Flammability limits temperature dependence of pure compounds in air at atmospheric pressure - Mendiburu, Andrés Z. [UNESP]; de Carvalho, João A. [UNESP]; Coronado, Christian R.; Roberts, Justo J. [UNESP] (Elsevier, 2017)
The objective of the present work is to study the temperature dependence of the flammability limits for pure compounds, and to develop a methodology to determine these limits in air at atmospheric pressure and at different initial temperatures of the mixture. A method to determine the lower flammability limits in those conditions was developed and compared with other methods available in the literature. The developed method shows an average absolute relative error of 3.25% and a squared correlation coefficient of 0.9928. Particularly, in the case of compounds with more than 5 carbon atoms, the method presents better accuracy than other available methods. Likewise, a method to determine the upper flammability limits was developed and compared with other widely accepted method. In this case, the developed methodology shows an average absolute relative error of 3.60% and a squared correlation coefficient of 0.9957, showing better accuracy than the available method.
Keywords: Combustion; Flammable properties; Semi-empirical method